Apoplastic mesophyll signals induce rapid stomatal responses to CO2 in Commelina communis. Issue 2 (8th April 2013) - Fujita, Takashi; Noguchi, Ko; Terashima, Ichiro
Summary: Previous studies have suggested that the mesophyll contributes to stomatal CO2 responses. The effects of changes in CO2 concentration (100 or 700 ppm) on stomatal responses in red or white light were examined microscopically in a leaf segment, an epidermal strip and an epidermal strip placed on a mesophyll segment of Commelina communis, all mounted on a buffer‐containing gel. In both red and white light, stomata of the leaf segment opened/closed rapidly at low/high CO2 . In red light, epidermal strip stomata barely responded to CO2 . In white light, they opened at low CO2, but hardly closed at high CO2 . Stomata of the epidermal strip placed on the mesophyll responded in the same manner as those on the leaf segment. Insertion of a doughnut‐shaped cellophane spacer (but not polyethylene spacer) between the epidermal strip and the mesophyll hardly altered these responses. Stomata in leaf segments treated with 3‐(3, 4‐dichlorophenyl)‐1, 1‐dimethylurea (DCMU), a photosynthesis inhibitor, did not open in red light, but opened/closed at low/high CO2 in white light. These results indicate that the apoplast transfer of 'mesophyll signals' and the stomatal opening at low CO2 are dependent on photosynthesis, whereas the stomatal closure at high CO2 is independent of photosynthesis.